UNMASKING TAX STRATEGIES: THE ROLE OF TRANSFER PRICING AND CAPITAL INTENSITY IN INDONESIA’S MINING SECTOR - Grediani, Evi; Jati , Budhi Purwantoro (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
Research related to Tax Avoidance is still an interesting topic to research, especially in Indonesia, which is trying to minimize tax avoidance practices. This research aims to examine the influence of transfer pricing and capital intensity on tax avoidance. The measurement of each variable is using the effective tax rate/ETR (for the tax avoidance variable), the amount of receivables from related parties (for the transfer pricing variable), and the ratio of fixed assets divided by total assets (for the capital intensity variable). For this research, the Author used a purposively selected sample, namely mining sector companies. The model was tested using multiple linear regression. The test results prove that transfer pricing has no influence, and capital intensity has a positive influence on tax avoidance. The research results can provide input for developing regulations related to tax avoidance practices.